Coexistence and bistability of a competition model with mixed dispersal strategy. (December 2020) - Wang, Yan'e; Nie, Hua; Wu, Jianhua
Abstract: In this paper, we investigate a Lotka–Volterra competition model with Danckwerts boundary conditions in a one-dimensional habitat where one species assumes pure random diffusion while another one undergoes mixed movement (both random and directed movements). We focus on the joint influence of advection rate, intrinsic growth rate and interspecific competition coefficient on the competition outcomes. It turns out that there exist some critical curves which separate the stable region of the semitrivial steady states from the unstable one. The locations of these curves determine whether coexistence or bistability occurs. More precisely, there are various tradeoffs between advection rate, intrinsic growth rate and interspecific competition coefficient that allow the transition of competition outcomes including competition exclusion, coexistence and bistability. We illustrate our results in various parameter spaces.